2021
DOI: 10.1038/s41598-021-82324-y
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial morbidity profile in a community based sample of low back pain patients

Abstract: Low back pain (LBP) is a major health concern and is closely associated with psychosocial morbidity and diminished Health-related quality of life (HRQoL). This is minimally investigated in community-based samples of developing nations like India. This study is aimed to specifically investigate the exposure-outcome associations between LBP and burden of disability (Modified Oswestry questionnaire (MODQ)), psychological morbidities (Depression, Anxiety and Stress Scale (DASS-21)), and HRQoL (Short Form -12 versi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The activities which included the patient in daily-life realms, participation in social events, leisure activities, work or occupation related were all moderately affected, and the patient had reduced the quality and participation instead. In all the factors, the study also showed that female patients were more affected than male, the physical activity, body mass index and job application correlated with the pain severity among the patients [15].…”
Section: Bps Approach In Indian Physiotherapymentioning
confidence: 74%
See 2 more Smart Citations
“…The activities which included the patient in daily-life realms, participation in social events, leisure activities, work or occupation related were all moderately affected, and the patient had reduced the quality and participation instead. In all the factors, the study also showed that female patients were more affected than male, the physical activity, body mass index and job application correlated with the pain severity among the patients [15].…”
Section: Bps Approach In Indian Physiotherapymentioning
confidence: 74%
“…The satisfaction and work required at the job was found deranged in more amounts, along with a higher prevalence towards depression, anxiety, and work stress. Patient noted that more than 70% of the individuals who complained of severe pain in the lower back, had a significant correlation with developing depression [15].…”
Section: Bps Approach In Indian Physiotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…5 A quarter of patients reported depression. 5 Despite various modalities options available for CLBP, management is usually suboptimal or inadequate. 5 Most of these modalities seem to mainly focus on the biomedical aspect of pain and overlook the mind-body component.…”
Section: Introductionmentioning
confidence: 99%
“…This same research group recently published a second study of 1502 subjects charting the psychological and social impact of low back pain in this nation of 1.366 billion people. (See Asrar et al, 2021. )…”
mentioning
confidence: 99%